Conservação em áreas privadas no Ceará: avaliação da efetividade da gestão, motivações e incentivos às reservas particulares do patrimônio natural - Moreira, Andréa de Sousa (2024)
In Brazil, Private Natural Heritage Reserves - RPPN are the only conservation units created privately on the initiative of owners who voluntarily decided to permanently conserve the natural heritage of their lands. On May 2, 2024, the National RPPN Confederation Panel indicated more than 1,868 RPPN protecting almost 836 thousand hectares in the country. However, the creation of these areas is not enough to guarantee the fulfillment of their conservation objectives. In this scope, initiatives have sought to involve owners interested in preserving the biodiversity and natural resources of their properties by establishing incentives to support the creation and management of RPPN. In Ceará, the RPPN Program was created to assist rural and urban landowners in the creation and management of these areas. In this context, the focus of the research was the analysis of the RPPN located in Cariri and Sertão do Inhamuns, established by the federal and state governments, in the period from 2014 to 2021. The main objective was to evaluate the effectiveness of the management of the RPPN and also identify the owners' motivations for creating RPPN, in addition to knowing the main incentives of the RPPN Program received by owners. To evaluate management effectiveness, indicators were previously selected, in accordance with the objectives of the RPPN and then optimal and current scenarios were constructed for each indicator associated with a standard scale based on Cifuentes et al., (2000). Among the results achieved, it was observed that the RPPN group obtained 61.58% of the optimal total and half of the areas were classified with lower standards (50.10 and 53.10%). Interviews with owners identified that the motivations for creating RPPN are mainly related to conservation with 41% of mentions. Regarding the RPPN Program, institutional support actions are little known by most owners and are limited to technical guidance for creation, without participation in management activities. These areas are important for the preservation of natural resources and the maintenance of essential ecosystem services, especially for preserving the springs and the Araripe Soldier, a bird, globally, considered critically endangered.